Body Weight Gain and Carcass Quality of the Hybrid Chicken Derived from the Crossing between Female F1 Kampung Super and Male F1 Kampung-Broiler - Utin Elsya Puspita; Hendry T.S.S.G. Saragih; Tety Hartatik; Budi Setiadi Daryono (Journal of Tropical Biodiversity and Biotechnology, 2021)
This research was conducted to observe the body weight gain and carcass quality of the hybrid chicken derived from the crossing between female F1 Kampung Super and male F1 Kampung-Broiler. The weekly weight gain for seven weeks and carcass quality, including breast yield, protein content, lipid content, moisture, and pH were measured with each group consists of six individuals. The chickens were slaughtered for meat quality measurements on the 7th week. The results showed that the hybrid chickens’ weight at the 7th week (888.22±139.63) was higher than layer (467.06±85.7) and pelung (436.39±42.33). The hybrid chicken’s breast yield (3.20%) was significantly higher than pelung’s (1.66%). These characteristics of hybrid chicken breast muscle lead to the conclusion that hybrid chicken is a potential alternative meat-type chicken with local chicken meat characteristics and has relatively fast growth.